Dance, girl, dance - Baum, Vicki 1888-1960; Ward, Edward 1900-1971 (<<The>> Criterion collection, 2020)
"Dorothy Arzner, the sole woman to work as a director in the Hollywood studio system of the 1930s and early ’40s, brings a subversive feminist sensibility to this juicily entertaining backstage melodrama. A behind-the-footlights look at friendship, jealousy, and ambition in the ruthless world of show business, Dance, Girl, Dance follows the intertwining fates of two chorus girls: a starry-eyed dancer (Maureen O’Hara) who dreams of making it as a ballerina, and the brassy gold digger (a scene-stealing Lucille Ball) who becomes her rival both on the stage and in love. The rare Hollywood picture of the era to deal seriously with issues of female artistic struggle and self-actualization, Arzner’s film is a rich, fascinating statement from an auteur decades ahead of her time." [criterion.com]
Original: USA 1940
Blu-ray special edition features: new, restored 4K digital transfer, with uncompressed monaural soundtrack ; new introduction by critic B. Ruby Rich ; new interview with filmmaker Francis Ford Coppola ; plus: an essay by critic Sheila O’Malley
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc